Nerve plane: An optimal surgical plane for laparoscopic rectal cancer surgery?. (September 2021) - Li, Kai; He, Xiaobo; Tong, Shilun; Zheng, Yongbin
Abstract: Radical resection for rectal cancer with total mesorectal excision has been widely recognized in mid-low rectal cancer. Although such surgery reduced the tumor recurrence rate and improved the survival rate of patients, the rate of urinary and sexual dysfunction was high after rectal cancer surgery, which might be attributed to pelvic autonomic nerve injury. The present study found that the pelvic autonomic nerves never exist alone. These are always surrounded by tiny capillaries and adipose tissue and covered by a thin layer of membranous tissue, leading to a continuous plane that should be preserved pelvic autonomic nerve from thermal damage, ischemic injury, nerve stretching, and chemical factors produced by local inflammatory effects. However, the completeness of the continuous plane is easily damaged intraoperatively in routine total mesorectal excision in rectal cancer. Postoperative urinary and sexual dysfunction might be closely associated with the injury of continuous plane. Therefore, the continuous plane should be protected and considered as the optimal surgical plane for rectal cancer surgery.